Semantic and Linguocultural Characteristics of Phraseological Units (In the Example of Uzbek and English Languages (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
The article is devoted to the study of semantic and linguocultural characteristics of phraseological units in English and Uzbek languages. Etymological and cultural features of phraseological units are considered on the example of Uzbek and English languages.